Efektifitas Motivasi Kerja Dan Kesejahteraan Sosial Terhadap Kinerja Karyawan Pada UMKM Fashion Ari Bagus Ikat Di Denpasar - Putu Chaitanya Framesty; Ni Luh Kardini; I Nyoman Gede Supraptha (Departement of Mathematics Education, 2024)
This study aims to determine the effect of Work Motivation and Social Welfare on Employee Performance at UMKM Fashion Ari Bagus Ikat in Denpasar. This study uses quantitative methods by distributing questionnaires to 30 respondents who are employees of UMKM Fashion Ari Bagus Ikatan in Denpasar. The sampling technique used is saturated sampling. The data analysis technique used is multiple linear regression. The results showed that Work Motivation T-count = 1.530 with a significance value of 0.013 had a positive and significant effect on Employee Performance. Social Welfare T-count = 9.488 with a significance value of 0.000 has a positive and significant effect on Employee Performance. Simultaneously, Work Motivation and Social Welfare F-count = 86,820 with a significance value of 0.000 have a positive and significant effect on Employee Performance with a determination value (R²) of 78% where Employee Performance is influenced by Work Motivation and Social Welfare variables, while the remaining 22% is influenced by other variables not analyzed in this study. The results of the study stated: 1) Work Motivation has a significant positive effect on performance; 2 )Social Welfare a significant positive effect on employee performance; The implication of this research is a moderate effect Work Motivation, Social Welfare on employee performance of UMKM Ari Bagus Ikat.